Strategi Manajemen Promosi dalam Peningkatan Jumlah Peserta Didik di Taman Qur’an Mutiara Hati Karawang - Amelia, Amelia; Darmiyanti, Astuti (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The aim of this study is to understand how the promotion management system works in terms of increasing the number of pupils present in the Qur’an Garden (TQ) Mutiara Hati Karawang. This research is a qualitative research that is carried out directly in the field with research subjects consisting of the head of the school. Data obtained is collected through observations as well as interviews between the researchers and the head. Mutiara Hati Karawang is one of the institutions located in Sukaluyu region, Telukjambe which is part of Karawang district and is precisely in a residential area. In an effort to promote its institutions, Mutiara Hati’s Qur’an Park (TQ) uses several promotional media, including printed media in the form of brochures or pamphlets, social media such as instagram and communication media, such as socialization of students’ parents or also known as parenting education for parents of students or for prospective parents of educators, where parents are given and equipped with knowledge and skills to help them in raising their children in the right, right, and proper way. The purpose of this promotion is to introduce the Koran Garden (TQ) to the communities in Karawang district in order to raise awareness of the parents who will enroll their children in the Kur'an Garden institutions. The promotion strategy of the Kur’an Garden educational institutions is interesting enough to be studied because although the institution is in a housing area, it will have a large number of pupils.